2011
DOI: 10.1103/physreva.83.053809
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency in an inhomogeneously broadenedΛtransition with multiple excited levels

Abstract: Electromagnetically induced transparency (EIT) has mainly been modelled for three-level systems. In particular, a considerable interest has been dedicated to the Λ-configuration, with two ground states and one excited state. However, in the alkali-metal atoms, which are commonly used, hyperfine interaction in the excited state introduces several levels which simultaneously participate in the scattering process. When the Doppler broadening is comparable with the hyperfine splitting in the upper state, the three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 55 publications
5
44
0
Order By: Relevance
“…In our experiment this corresponds to an upper temperature limit of several hundred mK. For even higher temperatures, the spectra become more complicated [20]. In addition, the large two-photon Doppler shift is detrimental to the spectral resolution.…”
Section: Numerical Simulationsmentioning
confidence: 74%
See 1 more Smart Citation
“…In our experiment this corresponds to an upper temperature limit of several hundred mK. For even higher temperatures, the spectra become more complicated [20]. In addition, the large two-photon Doppler shift is detrimental to the spectral resolution.…”
Section: Numerical Simulationsmentioning
confidence: 74%
“…However, for a description at larger precision (i.e., as desired for EIT-based thermometry) we will include also some additional off-resonant couplings (dark gray states in Fig. 1) [20]. There are two additional excited states |4 (corresponding to |F = 0,m F = 0 ) and |5 (corresponding to |F = 2,m F = 0 ) in the vicinity of state |3 .…”
Section: Theorymentioning
confidence: 99%
“…For instance, such gases can be used in quantum information science, in which cold clouds are promising objects for quantum memory problems (1)(2)(3)(4)(5). Theoretical results have also suggested that a high degree of vacuum squeezing of near resonance radiation may be obtained in such optically dense media through the action of the polarization self rotation effect (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the confidence one may have in a simple threelevel model we also need to examine to what degree one can map the complex multilevel hyperfine structure of 87 Rb to this reduced level scheme [35]. To do so, we need to take into account the different strengths of the various hyperfine transitions.…”
Section: B Predicted Absolute Values Of G and Gmentioning
confidence: 99%